The stability of money demand in China : evidence from the ARDL model - Baharumshah, Ahmad Zubaidi; Mohd, Siti Hamizah; Mansur, A. (Elsevier, 2009)
This study examines the demand for broad money (M2) in China using the autoregressive distributed lag (ARDL) cointegration framework. The results based on the bounds testing procedure confirm that a stable, long-run relationship exists between M2 and its determinants: real income, inflation, foreign interest rates and stock prices. Importantly, our results reveal that stock prices have a significant wealth effect on long- and short-run broad money demand; its omission can lead to serious misspecifications in the money demand function (MDF). This finding is consistent with the notion that asset inflation (deflation) has systematic influence on the pattern of monetary aggregates.